Meneguhkan Pancasila sebagai Ideologi Bernegara Mahasiswa Prodi Teknik Industri Universitas PGRI Adi Buana Surabaya: Indonesia - Billy Jack Sony; Suyono Suyono (Pusat Riset dan Inovasi Nasional, 2024)
The values of Pancasila are important to be practiced in the life of society, nation and state by every citizen of Indonesia. Until now, strong religious values have become the moral foundation of the life of the Indonesia nation. Human nature is highly respected and placed according to nature as a Created Creature of God Almighty. With its plurality, the Indonesia nation has a very heterogeneous cultural wealth. In Indonesia, the subject of Pancasila Moral Education (PMP) was once known, then changed to Pancasila and Citizenship Education (PPKn), and is currently known as Civic Education (PKn) in schools. In Higher Education, it is known that there are Pancasila Education and Civic Education courses. The learning model of Pancasila education in schools and universities has significant differences. The development of awareness of national and state life based on Pancasila values needs to be built and continue to be internalized to all Indonesia citizens because the challenges faced today, both domestically and abroad, are getting higher. It is important to pay attention to aspects of the educational process for the younger generation in fostering awareness of the values contained in Pancasila that are embraced so that they are not forgotten.